Variety of winter triticale «Slavetne»: origin, ecological sustainability, agrobiotic potential, source material - Москалець, В. В.; Лавров, В. В.; Москалець, Т. З.; Москалець, В. І.; Писаренко, П. В. (Scientific Progress & Innovations, 2012)
Agrobiological characteristics of winter triticale varietiy «Slavetne» are described. This variety was sorted out through the individual selection from hybrid combination («Augusto» х «Jaguar») x № 1364/93 according to quantitative (grain yield, number and weight of grain per spike, weight of the grain, 1000 grain weight) and qualitative (protein content, «raw» gluten) parameters of grain yield, ecological sustainability to pathogens of phytopathogenic diseases, abnormal phenomena of winterspring and summer periods, lodging. On the basis of «Slavetne» variety more frost resistant line «Slavetne pokraschene» was received by individual selection. The ability of winter triticale «Slavetne» to provide high yield at the sod-medium sandy loam and sod-podzolic sandy soils of Eastern and Central Polesie, the deep black soil and black soils of typical Northern and Central Forest-Steppe of Ukraine was proved.